PH stabilization of lactic acid fermentation via the glutamate decarboxylation reaction: Simultaneous production of lactic acid and γ-aminobutyric acid. Issue 10 (October 2015) - Zhao, Weirui; Huang, Jun; Lv, Changjiang; Hu, Sheng; Yao, Shanjing; Mei, Lehe; Lei, Yinlin
Graphical abstract